New Student Admission Selection Using the Weight Product Method as a Decision Support System at Permata Mulia Integrated Islamic Schoo - Kristiana, Novi Ayu; Aflaha, Dwi Sari Ida (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
This study aims to determine prospective new students through the weight product method as a decision support system at Permata Mulia Integrated Islamic School. This descriptive study uses data analysis techniques, including the weighted products method, as a decision support system. The steps taken include: determining the criteria in advance such as: age, independence, learning readiness, parental income, alum status, and the presence of siblings at the school; determining the weight of each criterion and normalizing the weight, the normalized weight values ​​sequentially from each criterion include: 0.26, 0.21, 0.16, 0.16, 0.11, and 0.11; determining the suitability rating between criteria and alternatives, calculating the S value by multiplying all the normalized weighted values, calculating the V value as an alternative preference which is then used to determine the ranking of each alternative. Based on the calculation results and ranking, A8 is the most recommended alternative because it meets all the proposed criteria. Meanwhile, A10 is in last place because it has the lowest score on the top priority criteria: age. Therefore, the selection of new students can be seen from the ranking results.